Modes and Approaches of Teaching and Learning Writing in BBS First Year (Journal of Management, 2022)
This article analyses the planning, process and application of Patterns for College Writing: A rhetorical reader and guide that has been prescribed as a textbook for BBS first year English course in Tribhuvan University Nepal since 2019. The analysis focuses on two aspects of the textbook: the making of the textbook to facilitate the students’ writing in the classroom and the practical outcome of the application of the textbook in real classroom setting. The first aspect concentrates on the textbook itself, whereas the second one is on a survey among the instructor of the same textbook. The analysis of the textbook shows that the course is well structured and so is useful for the writing class in the college level. But the survey has indicated the mismatch between the process designed in the book and its real application in the classroom. Some good practices have indicated that if the academic institutions, instructors and students work honestly for the students’ skill development, this textbook can be a good guide for developing an international level writing skill of students in Nepal.